Effects of changes in steel industry concentration - T. Bobenič; A. Bobenič Hintošová; L. Hliboká; I. Vasková (Metalurgija, 2015)
The paper on a basis of completed mergers and acquisitions within global steel industry presents changes in steel industry concentration and analyzes its effects on world trade with steel products and on prices of input materials as well as of output products. The analyses performed for the 1990 - 2012 period revealed that increased concentration in global steel industry did not lead to more intensive world trade with steel products, however it is connected with increase of finished products as well as of input material prices.